In situ remediation of Pb/Zn contaminated materials: field- and molecular-scale investigations - Baker, Lucas R. (Kansas State University, 2008)
The bioavailability of Pb and Zn is linked to the solubility of solid phases and other soil chemical characteristics, which is associated with their environmental risk, suggesting that in situ stabilization of these elements can be accomplished by influencing their chemistry. However, more research is needed to investigate the effectiveness of different soil amendments on reducing Pb and Zn bioavailability. A lab study was conducted to evaluate the effects of five different P amendments and time on Pb/Zn speciation in a contaminated soil using synchrotron-based techniques, while a field investigation studied the effects of composted beef manure on plant biomass production and the influence on microbial function, size, and community shifts. In the lab study, the Pb-phosphate mineral plumbogummite was found as an intermediate phase of pyromorphite formation, which has not been documented until now. Additionally, all fluid and granular P sources were able to induce Pb-phosphate formation, but fluid phosphoric acid (PA) was the most effective with time and distance from the treatment. However, acidity from PA increased the prescence of soluble Zn species, which can have negative environmental consequences. Granular phosphate rock (PR) and triple super phosphate (TSP) reacted to generate both Pb- and Zn-phosphates, with TSP being more effective at greater distances than PR. In the field study, compost additions of 269 Mg ha[superscript]1 significantly decreased bioavailable Zn, while increasing estimated available water, plant nutrients, and plant biomass as compared to a contaminated control and low addition of compost (45 Mg ha[superscript]1) over three years. Additionally, compost additions of 269 Mg ha[superscript]1 significantly increased microbial enzyme activities, nitrification, and microbial biomass over the contaminated control through the duration of the study. Increases in microbial activity and biomass are related to increases in total C, available water, and extractable P, while negative relationships were found with electrical conductivity and with bioavailable Zn. The addition of lime or lime plus bentonite with compost did not further reduce metal availability, increase plant biomass, or improve the size or function of microbial communities. High compost additions caused a slight shift in microbial community structure according to phospholipids fatty acid analysis. Increases in the mole percents of both Gram-positive (Gm[superscript]+) and Gram negative (Gm[superscript]-) bacteria were found depending on site. Microbial biomass of Gm[superscript]+, Gm[superscript]-, and fungi were also increased by high compost additions. Results indicate that large additions of compost are needed to increase microbial biomass, improve microbial activity, and re-establish a healthy vegetative community. This study proposes that organic matter and P amendments can be used to stabilize and reduce the bioavailability of heavy metals in soils and mine waste materials, but must be managed carefully and intelligently.
Keywords: In situ stabilization; Mine wastes; Synchrotron-based techniques; Pb and Zn; Agriculture, Soil Science (0481); Biogeochemistry (0425); Environmental Sciences (0768)